Enhancing aerobic composting of food waste by adding hydrolytically active microorganisms - Mironov, Vladimir; Zhukov, Vitaly; Efremova, Kristina; Brinton, William F. (Frontiers in Microbiology, 2024)
The biomass of native microorganisms in food waste (FW) suitable for accelerated composting is initially low and requires time for adaptation. Adding of efficient hydrolytic microorganisms should be able to enhance compost-specific microbial activity, adjust microbial community structure, and potentially hasten FW biodegradation. This study aimed to identify bacterial and fungal strains with growth characteristics suitable for accelerating FW composting. Over 7 weeks, FW was composted in a pilot-scale test, either inoculated at the start or on day 28 with three different mixtures of 10 autochthonous Bacillus and Penicillium spp. strains known for their high hydrolytic activity. The effects of inoculation were assessed by measuring the rate of carbon dioxide (CO2) and ammonia (NH3) production and also the increase in temperature due to spontaneous exothermic activity of the enhanced microbial population degrading FW. Inoculation with Bacillus spp., particularly B. amyloliquefaciens and B. subtilis, at the beginning of composting increased CO2 production nearly 3-fold while maintaining stable ammonia production and temperature. The high concentration of Bacillus relative to native FW microorganisms led to dominant fermentation processes even in the presence of oxygen, resulting in moderate heat release and elevated production of volatile organic compounds. Introducing Penicillium spp. at a later stage (day 28) increased CO2 production nearly 2-fold, along with higher NH3 levels and temperature. These findings highlight the significance of inoculation timing and microbial composition in regulating metabolic pathways during FW composting degradation, offering insights for designing effective microbial formulations for composting.